(untitled) (LEARNing Landscapes, 2016)
This narrative article describes key moments of meaningful encounters and learning through performative inquiry as university students and their professor engage in creative play and inquiry. What emerges is an understanding of how leadership might be performed, by students, by teacher within the classroom, within our lives. The rst performative inquiry experienced by the class and teacher occurs within the opening minutes of the rst day of class. Learning arrives through creative engagement and re ection, as students engage in creating one-act plays. An understanding and practice of reciprocal leadership, as conceptualized and experienced by author and students through their work together, invites us to reimagine ourselves in relationship and action with each other. Who we are in leadership, and how we come to understand performative inquiry as an emergent journey of collaborative learning through embodied creative action, dialogue, and re ection, is the heart of our exploration.